PENGARUH KEBIJAKAN PEMBINAAN PEMERINTAH TERHADAP KINERJA DAN STRUKTUR USAHA SUB SEKTOR INDUSTRI KECIL PENGGERAK EKONOMI DAERAH DI PROPINSI SUMATRA UTARA - Dr. Sonang Sitohang, MM (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
The objective of this research is to analyze and find empirical evidence of the affects of the government establishment policy, including; tecnical training support, government regulation support, capitalization support, marketing support, industrial and trade technical guidance supported for business performance and industrial structure unit development.The most significant findings is the influence of the business performance on the business structure 0,8037. It is the highest coefficient value among the others. It proves that government is successful in arranging and managing its establishment by training support, government rules, capitalization, marketing, and industrial and trade technical guidance support as stated in Regulation No. 9, 1995 on the Small and Medium Enterprise Affair by increasing business structure from micro industry to small industry. Besides the main finding above, there are other research findings; the positive significance of the government rules on the business performance and  business structure that do not support Vasant Desai Theory (2003), and the positive significance of the effects of the industrial and trade guidance on the business performance and doesn’t  support Mulyadi research (1999).